2003
DOI: 10.1212/01.wnl.0000078815.03224.57
|View full text |Cite
|
Sign up to set email alerts
|

Language lateralization by Wada test and fMRI in 100 patients with epilepsy

Abstract: Comparing the determination of language dominance using fMRI with results of the Wada test in 100 patients with different localization-related epilepsies, the authors found 91% concordance between both tests. The overall rate of false categorization by fMRI was 9%, ranging from 3% in left-sided temporal lobe epilepsy (TLE) to 25% in left-sided extratemporal epilepsy. Language fMRI might reduce the necessity of the Wada test for language lateralization, especially in TLE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

23
254
2
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 380 publications
(286 citation statements)
references
References 7 publications
23
254
2
4
Order By: Relevance
“…Such data have led some experts to conclude that fMRI may be better suited for localizing expressive language areas within the frontal lobe than receptive language areas within temporal lobe regions ((68,69), but see (70,71)). Overall, results suggest approximately 90% concordance between fMRI and IAP lateralization in patients with TLE, with less impressive results in patients with extratemporal epilepsy (72). In addition, there are data demonstrating that fMRI language activations complement electrocortical stimulation findings (73) and predict post-operative naming decline (74).…”
Section: Fmrimentioning
confidence: 94%
“…Such data have led some experts to conclude that fMRI may be better suited for localizing expressive language areas within the frontal lobe than receptive language areas within temporal lobe regions ((68,69), but see (70,71)). Overall, results suggest approximately 90% concordance between fMRI and IAP lateralization in patients with TLE, with less impressive results in patients with extratemporal epilepsy (72). In addition, there are data demonstrating that fMRI language activations complement electrocortical stimulation findings (73) and predict post-operative naming decline (74).…”
Section: Fmrimentioning
confidence: 94%
“…In recent years, several studies have compared fMRI and the IAP with respect to language lateralization, or evaluated the ability of fMRI to localize language functions in children and adults with epilepsy [12][13][14][15][16][17][18][19][20][21][22][23][24]. These and other authors used various language fMRI tasks including semantic decision [14,16,21,[25][26][27], verb generation/verbal fluency [13,19,20,23,[28][29][30], word generation [15,18,22,24], and sentence reading [17,31].…”
Section: Introductionmentioning
confidence: 99%
“…These and other authors used various language fMRI tasks including semantic decision [14,16,21,[25][26][27], verb generation/verbal fluency [13,19,20,23,[28][29][30], word generation [15,18,22,24], and sentence reading [17,31]. Some studies have also reported the use of more than one fMRI paradigm for language localization and lateralization [10,12,13,29,32,33], but the results of these studies have been mixed, with some tasks showing good and some poor correlation with the results of IAP.…”
Section: Introductionmentioning
confidence: 99%
“…Some newer methods include event-related brain potentials [4] and whole-head magnetoencephalography [5][6][7]. The other alternative activation techniques are based on hemodynamic responses to language activation, such as functional transcranial Doppler [8], single-photon-emission computed tomography [9], positron emission tomography [10], near-infrared spectroscopic mapping [11], and functional magnetic resonance imaging [12]. All of these newer methods have variable limitations, and none have yet supplanted the Wada test as the ''gold standard" for lateralizing cerebral language dominance.…”
Section: Introductionmentioning
confidence: 99%